#TITLE_ALTERNATIVE# - HUSNI (NIM 12103021), BUSTANIL
Blasting activities that done by XYZ company are to explode the bedrock, where the result of the explosion will be used as one of civil material for road construction and also as civil material for loading point location. Blasting activities are done near to slag dump area where constructed by considering the tremor factor scale 0.2 g. The ground wave that resulted by the blasting activities is predicted causing the destruction of slag dump. Tremor factor scale 0.2g that used as preserve construction of slag dump become the benchmark to compare the wave that caused by the explosion (blasting activities). To know the comparison between the ground wave (earthquake) and blasting wave, analysis of each waveÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â’s component is done. Blasmate is the tool that used to measure the wave. The data of blasting wave that has been got is being proceed and analyzed for its PPV, PPA, and SD of each waveÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â’s components (transversal, vertical, and longitudinal). For earthquake (tremor), the characteristic of each earthquake components are being analyzed, which are body waves (compression and shear) and surface waves (Rayleigh/vertical and love). The wave that has same characteristics is the vertical wave. Vertical wave is not influenced by the direction of blasting measurement. By using the formula of vertical PPA. The recommended safety space from slag dump if the blasting pattern is 72.5 kg using maximum loaded per delay is 140 m.